2016
DOI: 10.1038/srep23898
|View full text |Cite
|
Sign up to set email alerts
|

Fano resonance of Li-doped KTa1−xNbxO3 single crystals studied by Raman scattering

Abstract: The enhancement of functionality of perovskite ferroelectrics by local structure is one of current interests. By the Li-doping to KTa1−xNbxO3 (KTN), the large piezoelectric and electro-optic effects were reported. In order to give new insights into the mechanism of doping, the microscopic origin of the Fano resonance induced by the local structure was investigated in 5%Li-doped KTN single crystals by Raman scattering. The coupling between the continuum states and the transverse optical phonon near 196 cm−1 (Sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
40
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 46 publications
(86 reference statements)
1
40
0
Order By: Relevance
“…Recently, Rahaman et al reported the breaking of local symmetry and the microscopic origin of the CP in the cubic phase of a high quality KLTN/5/27 crystal by the observation of E(x,y) symmetry of PNRs with the rhombohedral R3m symmetry using Raman scattering. 15 It is important to note that the intensity of the LA mode is relatively weak and it exhibits asymmetric nature (Fig. 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Rahaman et al reported the breaking of local symmetry and the microscopic origin of the CP in the cubic phase of a high quality KLTN/5/27 crystal by the observation of E(x,y) symmetry of PNRs with the rhombohedral R3m symmetry using Raman scattering. 15 It is important to note that the intensity of the LA mode is relatively weak and it exhibits asymmetric nature (Fig. 1).…”
mentioning
confidence: 99%
“…11,12 The existence of PNRs in KTN and Li-doped KTN was reported by various measurements. [13][14][15][16][17][18][19] In the cubic phase, the PNRs are characterized by two temperatures. First, the Burns temperature, T B , at which the dynamic PNRs begin to appear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to identify the local structural symmetry of PNRs, the angular dependence of Raman scattering (one of ILS) combined with Raman tensor analysis can be a very powerful technique, because it measures the scattering intensity with respect to the polarization direction of an incident light. Recently, the local symmetry of CPs and some other Raman modes in a paraelectric cubic phase related to rhombohedral PNRs were identified by the angular dependence of Raman scattering in Li-doped KTN18 and PMN19 single crystals. The angular dependences of Raman spectra of PT and PMN-33PT were also measured in the tetragonal phase to identify the symmetry of the modes2021.…”
mentioning
confidence: 99%
“…To observe the variation of the diagonal and off-diagonal elements in the Raman tensor in the vicinity of a phase transition point, it is necessary to measure both the polarized (VV) and depolarized (VH) scattering separately18. So far, the low-frequency ILS studies on a phase transition have been performed by using VV or unpolarized light scattering14232425262728.…”
mentioning
confidence: 99%